Radical Positioning : an international exhibition on taking a radical (art)position on questions of the social, political and historical. - Grzinic, Marina; Pavel House Laafeld, Potrna ([S.l.] : Pavlova hisa, 2004)
Caspar, Barbara ; Bolt, Catrin ; Rych, David ; Ostojic, Tanja ; Haupt, Philipp ; Mayer, Ralo ; Irwin ; Holub, Barbara ; Rajakovics, Paul ; Vujinovic, Tanja ; et al.
Radical Positioning, Pavel House Laafeld, Potrna, 3 July - 25 September 2004
kunstcatalogus